Attenuated Heart Rate Response is Associated with Hypocretin Deficiency in Patients with Narcolepsy - Sorensen, Gertrud Laura (Associated Professional Sleep Societies, LLC, 2013)
STUDY OBJECTIVE: Several studies have suggested that hypocretin-1 may influence the cerebral control of the cardiovascular system. We analyzed whether hypocretin-1 deficiency in narcolepsy patients may result in a reduced heart rate response. DESIGN: We analyzed the heart rate response during various sleep stages from a 1-night polysomnography in patients with narcolepsy and healthy controls. The narcolepsy group was subdivided by the presence of +/− cataplexy and +/− hypocretin-1 deficiency. SETTING: Sleep laboratory studies conducted from 2001-2011. PARTICIPANTS: In total 67 narcolepsy patients and 22 control subjects were included in the study. Cataplexy was present in 46 patients and hypocretin-1 deficiency in 38 patients. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: All patients with narcolepsy had a significantly reduced heart rate response associated with arousals and leg movements (P < 0.05). Heart rate response associated with arousals was significantly lower in the hypocretin-1 deficiency and cataplexy groups compared with patients with normal hypocretin-1 levels (P < 0.04) and patients without cataplexy (P < 0.04). Only hypocretin-1 deficiency significantly predicted the heart rate response associated with arousals in both REM and non-REM in a multivariate linear regression. CONCLUSIONS: Our results show that autonomic dysfunction is part of the narcoleptic phenotype, and that hypocretin-1 deficiency is the primary predictor of this dysfunction. This finding suggests that the hypocretin system participates in the modulation of cardiovascular function at rest. CITATION: Sorensen GL; Knudsen S; Petersen ER; Kempfner J; Gammeltoft S; Sorensen HBD; Jennum P. Attenuated heart rate response is associated with hypocretin deficiency in patients with narcolepsy. SLEEP 2013;36(1):91–98.